Multi-classification based Alzheimer's disease detection with comparative analysis from brain MRI scans using deep learning - Kabir, Azmain; Kabir, Farishta; Mahmud, Md. Abu Hasib; Sinthia, Sanzida Alam; Azam, S. M. Rakibul (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.